FEATURE OF CORONAVIRUS DISEASE IN PATIENTS WITH ARTERIAL HYPERTENSION AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE - N.K. Pokrovska; H.M. Shcherbata; O.S. Kapustynska; Y.Ya. Sklyarov (Медична наука України, 2021)
Relevance. The combination of coronavirus disease (COVID-19) with arterial hypertension (AH)  and chronic obstructive pulmonary disease (COPD) is associated with decreased saturation, general clinical signs of inflammation, coagulopathies and worsens the course and prognosis of the disease. That is why it is important to identify all possible risk factors for complicated pathology for the prevention and timely treatment of this category of patients.